Development of automated measurement system for ultra-high resistance above 1 teraohm - Zhu, Xiao Ming. (2012)
More and more requirement from industrial manufactures demands high precision measurements of high-value direct-current (DC) standard resistors, typically in the range of 10 MΩ up to 100 TΩ. These standard resistors are used as reference standards for the calibration and performance verification of various DC voltage calibrators, ohmmeters, and digital multimeters (DMM), and also as transfer standards in the low electrical current measurement, e.g., below 100 pA. In the National Metrology Centre (NMC), the primary measurement laboratory of Singapore, in order to extend the high resistance measurement capability from 1 TΩ to 100 TΩ, an ultra-high resistance measurement system has been developed based on dual source Wheatstone bridge in this final year project. A new system configuration connection has been designed and implemented with a new junction box. A control software program has been implemented based on LabView to fully automate the measurement process. Performance verification and software validation have been done in the project, showing that the developed measurement system is capable and efficient enough to make accurate high resistance measurement on the range 1 TΩ to 100 TΩ within the uncertainty requirements.